2008
DOI: 10.1103/physrevlett.100.064801
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Photofield Emission from Needle Cathodes for Low-Emittance Electron Beams

Abstract: Illumination of a ZrC needle with short laser pulses (16 ps, 266 nm) while high voltage pulses (-60 kV, 2 ns, 30 Hz) are applied, produces photo-field emitted electron bunches. The electric field is high and varies rapidly over the needle surface so that quantum efficiency (QE) near the apex can be much higher than for a flat photocathode due to the Schottky effect. Up to 150 pC (2.9 A peak current) have been extracted by photo-field emission from a ZrC needle. The effective emitting area has an estimated radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 20 publications
(19 reference statements)
0
61
0
Order By: Relevance
“…Ganter et al (2008) have performed photo-field emission tests from a single ZrC needle. With 16 ps long laser pulses at 266 nm, they have obtained electron pulses with up to 150 pC and a peak current of 2.9 A at 60 keV in pulsed high-voltage operation, at a repetition rate of 30 Hz and a tip radius r ≈ 50 µm.…”
Section: Current Status Of Tip-based and Tip Array-based Approachesmentioning
confidence: 99%
“…Ganter et al (2008) have performed photo-field emission tests from a single ZrC needle. With 16 ps long laser pulses at 266 nm, they have obtained electron pulses with up to 150 pC and a peak current of 2.9 A at 60 keV in pulsed high-voltage operation, at a repetition rate of 30 Hz and a tip radius r ≈ 50 µm.…”
Section: Current Status Of Tip-based and Tip Array-based Approachesmentioning
confidence: 99%
“…Despite the low bunch charge (∼fC) supported by DLAs, successful FEL operation appears feasible [26]; source development is needed, as in other FEL approaches [18,27]. Moreover, the realization of accelerating, deflecting, focusing and bunching elements for non-relativistic electrons could lead to a new generation of electron optics with applications in ultrafast electron diffraction experiments and time-resolved electron microscopy.…”
mentioning
confidence: 99%
“…Due to their micron-scale size, DLA structures require and support electron beams with normalized emittance values in the nm-range [23]. Therefore, a nonrelativistic DLA section in combination with an ultralow emittance electron source, such as a laser-triggered needle cathode with an intrinsic emittance of ∼50 nm [18], is crucial for the injection of high-quality electron beams into the relativistic section of the DLA. A common laser source, amplified in various sections, can be used to drive the electron gun, the non-relativistic and the relativistic DLA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To combat this issue, enhanced local fields in the vicinity of metallic nano-structures and longer wavelength drivers can be exploited to significantly reduce the optical intensities required to induce emission and accelerate electrons to high energies. Indeed, during the last decade, numerous studies have explored strong-field physics by coupling femtosecond laser pulses to nanostructured solids, particularly metallic nano-tips [140][141][142][143][144][145][146][147][148][149][150][151][152][153][154]. The results of those investigations demonstrated that, with proper modification, much of the basic physics underlying laser induced ionization of atomic and molecular gases also applies to laser-induced electron emission from solids.…”
Section: Chapter 5 High-energy Electron Emission From Metallic Nano-mentioning
confidence: 99%